Sistem Pendukung Keputusan Pengangkatan Tamping Pada Tanjung Gusta Medan Menerapkan Metode Analytic Process Network (ANP) - Abdurahman, Husin (Jurnal Sains dan Teknologi Informasi, 2022)
This study aims to build a support system in the main decision making for the appointment of Tamping at Tanjung Gusta Medan. Tamping is a prisoner who assists correctional officers in carrying out coaching activities in prisons. The research data used were obtained from Tanjung Gusta Prison. This decision support system was built using vb.net 2008 by implementing the Analytic Network Process (ANP). The Analytic Network Process (ANP) method is a method that is applied to various problems including decision making, prediction or forecasting, evaluation, mapping, resource allocation and so on. The results of the study are useful to help the leadership of the Tanjung Gusta Medan prison choose quality tamping and can provide direction to every convict at the Tanjung Gusta Medan prison